Post-pandemic Mexican labor market outlook: asymmetric recovery - Jiménez-Bandala, Carlos Alberto; Andrade, Luis Antonio; Balam, Alia; Soto-Rodríguez, José Antonio; Guzmán-Cruz, Jose Emiliano (Revista Internacional de Salarios Dignos, 2021)
After the period of confinement to prevent the spread of the CoViD-19 virus, the reopening in the new normal poses the challenge of economic recovery, in that sense this paper analyzes the dynamics of the post-pandemic Mexican labor market through several econometric modeling including multivariate linear models and time series analysis. The main results show that the recovery of both formal and informal jobs is being faster than expected, however, it presents asymmetries that reveal the pre-existing structural uneven conditions. While the northern states would achieve this summer to reach the pre-pandemic level; the southern states would do so until the following year. At the end, intervention recommendations are proposed to reduce the gaps between north-south.